Prisão e tortura em terra estrangeira: a colaboração repressiva entre Brasil e Uruguai (1964-1985) - Cassol, Gissele (2008)
Latin America was made stage for the quarreling between the capitalist and socialist systems starting circa the middle of the century XX, during the Cold War. Such ideological struggle had as one of their main outcomes the ascension of civil-military dictatorships in many Latin countries. Those regimes, fundamentally based on the North American National Security Doctrine (NSD), they have accomplished a brutal Terror of State to face their political opponents. The combat to the internal enemy extolled by NSD provoked the extinction of the political borders; in its place, they would just be delimited ideological borders. Following that logic it was the formation of a web of relationships among the repressive apparatuses of those dictatorships, whose apex has been established with the creation of the Condor Operation, in 1975. It is in that context that locates the gist of this dissertation: the existent repressive collaboration between Brazil and Uruguay during the period understood between 1964 and 1985. Although Uruguay became a dictatorship only starting from 1973, since ends of the decade of 1960 it already cooperated with the Brazilian regime watching, arresting and even torturing Brazilian political opponents exiled in his/her territory. The high number of cases of arrested Brazilians in Uruguay in that period attests that relationship and evidences that the repressive collaboration among those two countries did not depend exclusively on the Condor Operation even though having been facilitated by it later. The present study intends to demonstrate, starting from the analysis of cases of arrested Brazilians in Uruguay and of arrested Uruguayans in Brazil between 1964 and 1985, how the repressive collaboration among those two countries was, under the scope of NSD and of the practices of Terror of State.